Bureaucracy and the balanced scorecard in health care settings - Costa Oliveira, Helena (2022)
Purpose – We explore the relationship between the Balanced Scorecard (BSC) and neo- bureaucracy by investigating whether the operationalization of the BSC incorporates ‘neo- bureaucratic’ ideas; and whether the BSC implemented in a Portuguese Local Health Unit (LHU) evidences a neo-bureaucratic approach. Design/methodology/approach – We conduct semi-structured interviews with LHU staff and analyse documents to assess whether features of bureaucratic organization were evident in the use of a BSC by the LHU. Findings – We found nine bureaucratic features evident in the LHU’s BSC. These were systematization, rationality, authority, jurisdiction, professional qualification, knowledge, discipline, transparency, and accountability. The BSC used at the LHU evidenced a neo- bureaucratic approach. Originality/value – Our study helps to demystify bureaucracy and overcome prevailing prejudices regarding some of its principles. Health care managers should recognize and endorse neo-bureaucratic principles in developing a BSC. They should recognize the BSC as involving a neo-bureaucratic approach. The BSC is a valuable management tool that hospital managers should find useful fostering flexibility, collaboration, innovation and adaptation – all of which should help lead to improved health care outcomes.